169 A prospective interventional study evaluating awareness and knowledge about genetic aspects of breast cancer and the effect of educational intervention: a real-life experience. (13th November 2020) - Kumar, N; Mishra, A; Deo, S
Abstract : Introduction: Recent advances in understanding the genetic basis of breast cancer have opened new treatment pathways for risk reduction. Literacy rates are low in India in contrast to western societies. Hence separate studies to gauge awareness and acceptance of genetic counseling and testing are required. This is likely the first educational interventional study involving the Indian breast cancer population for assessment of knowledge regarding the genetic aspect of breast cancer. Methods: It was a prospective interventional study performed with a total sample size of 200 breast cancer patients, enrolled from July 2018 to December 2019 using a structured questionnaire and educational material regarding genetic factors. Institutional ethics committee approval was taken (No- IECPG-182/10.05.2018). Study Phases Pre–intervention assessment– Questionnaire–based assessment of awareness and knowledge had done with prior informed consent. Educational Intervention– Brief descriptive educational material about breast cancer and its risk factors, screening, treatment, genetic aspects and prophylactic interventions were provided. Post–Intervention assessment –After 5–7 days of educational intervention, patients were re–assessed with the same questionnaire. Results: Two hundred patients were recruited in the study of whom 150 (75%) were sporadic and 50 (25%) were familial or hereditary. The response of the patients to the questionnaire and the effect of the educational intervention has been depicted in the following table 1 . Conclusion: There is a significantly low level of awareness among breast cancer patients. The single short educational intervention had a significant impact on increasing awareness and knowledge particularly in terms of risk factors, screening, management, familial breast cancer, genetic testing, etc.